2020
DOI: 10.18295/squmj.2020.20.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Risk Factors, Symptoms and Barriers to Seeking Medical Help for Cervical Cancer among Omani Women Attending Sultan Qaboos University Hospital

Abstract: Objectives: This study aimed to assess knowledge and attitudes among Omani woman regarding cervical cancer risk factors and symptoms as well as barriers to them seeking medical help. Methods: This cross-sectional study was conducted between December 2017 and March 2018 at the Sultan Qaboos University Hospital (SQUH) in Muscat, Oman. A validated Arabic-language version of the Cervical Cancer Awareness Measure questionnaire was used to collect data from 550 Omani women visiting SQUH during the study period. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 12 - 22 They collectively suggest that while most women have heard of cervical cancer, they have low knowledge of its specific symptoms and screening tests. 12 - 14 , 17 Other studies have indicated that the awareness of cervical cancer is greater among women than that of the availability of diagnostic tests. 23 , 24 The current study was conducted to determine levels of knowledge, attitudes, and screening practices related to cervical cancer and its screening among Omani women visiting a FMPH clinic.…”
Section: Discussionmentioning
confidence: 99%
“… 12 - 22 They collectively suggest that while most women have heard of cervical cancer, they have low knowledge of its specific symptoms and screening tests. 12 - 14 , 17 Other studies have indicated that the awareness of cervical cancer is greater among women than that of the availability of diagnostic tests. 23 , 24 The current study was conducted to determine levels of knowledge, attitudes, and screening practices related to cervical cancer and its screening among Omani women visiting a FMPH clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the implementation of Pap smear screening in LMICs is challenging due to poor attendance and lack of awareness of the importance of this type of screening in the prevention and early detection of cervical cancer [ 8 ]. Previous studies conducted in LMICs have indicated that women may encounter several barriers to cervical cancer screening, including poor knowledge regarding the importance of the HPV vaccine or Pap smear test, negative attitudes towards cervical cancer-related risk factors (particularly HPV infection), fear of the results, and concern regarding the gender of the doctor performing the screening test [ 9 11 ]. In Oman, the HPV vaccine is not yet included in the Expanded National Immunization Program and is therefore not systematically provided by government-funded health institutes under the national Ministry of Health [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the implementation of Pap smear screening in LMICs is challenging due to poor attendance and a lack of awareness of the importance of this type of screening in the prevention and early detection of cervical cancer [8]. Previous studies conducted in LMICs have indicated that women may encounter several barriers to cervical cancer screening, including poor knowledge regarding the importance of the HPV vaccine or Pap smear test, negative attitudes towards cervical cancer-related risk factors (particularly HPV infection), fear of the results, and concern regarding the gender of the doctor performing the screening test [9][10][11].…”
Section: Introductionmentioning
confidence: 99%